2011
DOI: 10.1097/scs.0b013e318211519e
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Treatment of Odontogenic Myxoma

Abstract: Odontogenic myxomas (OMs) are nonencapsulated rare benign tumors that can occur in gnathic bones. They are locally invasive and have a high recurrence rate. Radiologically, OMs show a multilocular (in the majority of cases) or unilocular radiolucency, with either distinct or poorly defined margins. Histopathologically, OMs are characterized by spindle-, wedge-, or stellate-shaped cells loosely arranged in an abundant mucoid background. Myxomas are mainly asymptomatic. Radical surgery, excision, and enucleation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Although OM is a benign tumor, radical treatment is needed because the rate of local recurrence ranges from 10% - 33% [3-5]. Surgical resection with a minimum bone margin of 1 cm has been advocated [6-9], but emerging evidence suggests that a more conservative surgical approach will result in acceptable recurrence rates with less patient morbidity if follow-up can be over the long term [7, 10-12]. However, little has been reported about the actual long-term follow-up of patients with OM after conservative surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Although OM is a benign tumor, radical treatment is needed because the rate of local recurrence ranges from 10% - 33% [3-5]. Surgical resection with a minimum bone margin of 1 cm has been advocated [6-9], but emerging evidence suggests that a more conservative surgical approach will result in acceptable recurrence rates with less patient morbidity if follow-up can be over the long term [7, 10-12]. However, little has been reported about the actual long-term follow-up of patients with OM after conservative surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zanetti, et al strongly suggested conservative treatment should involve enucleation of the lesion with a wide curettage of normal tissue or a generous amount of apparently uninvolved surrounding tissue, or even peripheral osteotomy, as this has the advantage of preserving vital structures and maintaining oral function [24].…”
Section: Discussionmentioning
confidence: 99%
“…The above case illustrates the merits of a less than fully radical approach to treatment. In the absence of an evidence-based solution, it is best to follow Zanetti et al in using a conservative approach initially and progressing to peripheral osteotomy if recurrence occurs 11. Resections could perhaps be attempted following a recurrence subsequent to a conservative surgery.…”
Section: Discussionmentioning
confidence: 99%